The essence and the meaning of the "education marketing" - Kulić, Radivoje N.; Milačić, Srećko P. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The growing influence of economic and organizational theory on modern trends in education, that is particularly evident in the last few decades, has also affected the implementation of marketing orientation in this area. The dilemmas and misunderstandings concerning the application of marketing concepts in education as a specific sphere of social activity where the use of market mechanisms wasn't optimal, were not explained. Nonetheless, such a development can not completely be ruled out, noting that the application of this concept in education has a much broader meaning and significance. To put it another way, it means that the concept of marketing in education is not exclusively oriented towards profit making, but it is primarily focused on motivation and the development of valuable personality traits, and the formation  of diverse interests and a wide range of educational needs of potential users. In such developing higher education sector, and institutions for adult's education,  one can apply the "marketing principles and strategies", in the interests of these institutions, but also in the interests of the users of educational services and the society in general.
Keywords: adult education; higher education; user; educational service; marketing in education; marketing